Technological Change and Market Conditions: Evidence from Bitcoin Fork. (18th November 2022) - Kim, Hyeonoh; Yi, Eojin; Lee, Daeyong; Ahn, Kwangwon
Abstract : This article examines the impact of technological changes to cryptocurrency—known as "forking" that triggers blockchain splits—on market conditions. Despite the explicit distinction in log return distributions between the two splitting blockchains, adopting new technology does not result in a disparity in market conditions: no significant difference exists in market efficiency and long-term market equilibrium between the two splitting blockchains. Technological changes accompanying market separation do not impede the underlying uniformity in market conditions. The findings suggest that mutual information flows linked to market liquidity explain the results between the new and old forks.